Wind effects on large cooling tower in velocity fields of different non-stationary levels. Issue 9 (21st May 2021) - Cheng, XiaoXiang; Zhao, Lin; Ge, YaoJun; Wu, Gang
Abstract : The non-stationarity of the realistic wind velocity field strongly influences wind effects on structures. Related research studies are limited, as it is difficult to simulate non-stationary wind velocity fields using wind tunnel model tests and numerical simulations. In this paper, wind effects on a 167 m high cooling tower in velocity fields of different non-stationary levels are investigated based on a full-scale measurement campaign. First, numerical analyses are employed to identify the quasi-steady region on circular cylindrical structures. Second, wind velocity samples are extracted from the full-scale wind pressure samples measured in the quasi-steady region on the actual large cooling tower, and quantitatively evaluated for their non-stationary levels using a wavelet packet transform-based indicator. Third, effects of the non-stationarity of the velocity field on wind loads on the large cooling tower are revealed based on different non-stationarity cases. Through these works, it is found that the non-stationary level of the wind velocity field largely influences wind effects on the cooling tower in most cases, and the wind effects obtained in a velocity field of high non-stationarity are generally more unfavourable than those obtained in a velocity field of low non-stationarity.